Es erróneo hacer una asociación directa entre la detección de Helicobacter spp.y gastritis en caninos - Suárez-Esquivel, Marcela (2017)
It has been proposed that Helicobacter may play a significant role in the generation of gastritis and cancer in dogs. However, despite several independent efforts, there is still controversy regarding the true ability of Helicobacter to cause gastric lesions in these animals. The foregoing is due in part to the fact that gastritis is a multifactorial disease. Studies focused on naturally acquired infections have been unable to establish a positive correlation between Helicobacter colonization and gastritis. Establishing a clear association between the presence of Helicobacter and gastritis may be difficult due to the following reasons: (i) taxonomy of the genus Helicobacter remains unclear, (ii) virulence factors of Helicobacter species that colonize dogs are not well known, and (iii) simultaneous infections have been reported with several species of Helicobacter. Current knowledge in taxonomy and pathogenesis of Helicobacter species is insufficient to differentiate between pathogenic and non-pathogenic strains. Therefore, no direct association should be made between the detection of Helicobacter and gastritis.